Marasmius tricystidiatus sp. nov. (Agaricales, Marasmiaceae) and its morphological and phylogenetic relationship with Marasmius jalapensis - Ramírez, Natalia A.; Niveiro, Nicolás; Salvador-Montoya, Carlos A.; Piris Da Motta, Fátima; Pérez, M. Laura; Popoff, Orlando F. (Phytotaxa, 2021)
Morphological and phylogenetic analyses were performed on recently collected Marasmius specimens including specimens previously determined as Marasmius jalapensis in northern Argentina and Paraguay. A description of a new species for northern Argentina and Colombia and a new morphological delimitation of M. jalapensis with a more restricted distribution range are proposed. Marasmius tricystidiatus sp. nov. is characterised by its yellowish and slightly sulcate pileus, medium-sized basidiomata, setae in all tissues and cheilocystidia of three types, viz., Siccus-type broom cells, cheilosetae, and transitional elements; M. jalapensis, the closest species, is similar in pileus coloration and presence of setoid cystidia in all tissues, but mainly differs in having only cheilosetae and broader basidiospores on average. Both species are closely related and belong to sect. Globulares subsect. Leonini, but the relationships within the latter still must be resolved.